TKU-PSO: An Efficient Particle Swarm Optimization Model for Top-K High-Utility Itemset Mining - Carstensen, Simen; Chun-Wei Lin, Jerry (International Journal of Interactive Multimedia and Artificial Intelligence, 2024)
Top-k high-utility itemset mining (top- HUIM) is a data mining procedure used to identify the most valuable patterns within transactional data. Although many algorithms are proposed for this purpose, they require substantial execution times when the search space is vast. For this reason, several meta-heuristic models have been applied in similar utility mining problems, particularly evolutionary computation (EC). These algorithms are beneficial as they can find optimal solutions without exploring the search space exhaustively. However, there are currently no evolutionary heuristics available for top-k HUIM. This paper addresses this issue by proposing an EC-based particle swarm optimization model for top-k HUIM, which we call TKU-PSO. In addition, we have developed several strategies to relieve the computational complexity throughout the algorithm. First, redundant and unnecessary candidate evaluations are avoided by utilizing explored solutions and estimating itemset utilities. Second, unpromising items are pruned during execution based on a thresholdraising concept we call minimum solution fitness. Finally, the traditional population initialization approach is revised to improve the model’s ability to find optimal solutions in huge search spaces. Our results show that TKU-PSO is faster than state-of-the-art competitors in all datasets tested. Most notably, existing algorithms could not complete certain experiments due to excessive runtimes, whereas our model discovered the correct solutions within seconds. Moreover, TKU-PSO achieved an overall accuracy of 99.8% compared to 16.5% with the current heuristic approach, while memory usage was the smallest in 2/3 of all tests.
Keywords: data mining; evolutionary computation; fitness estimation; particle swarm optimization; threshold-raising strategy; top-k high-itility itemset; IJIMAI